The generous years remembrances of a frontier boyhood. - Huntley, Chet, 1911-1974. (New York, Random House, 1968)
Reminiscences by a well known news commentator of his boyhood experiences in Montana during and immediately following World War I.
Keywords: Huntley, Chet -- 1911-1974.; Huntley, Chet -- 1911-1974 -- Childhood and youth; Frontier and pioneer life -- Montana; Montana -- Social life and customs